Analisis Pengaruh Ukuran Lantai Muatan Timbangan Terhadap Nilai Error Pada Pengujian Eksentrisitas Timbangan Elektronik Sesuai OIML R76 - Geston Bakti Muntoha; Danang Erwanto; Dian Septi Nur Afifah (Jurnal Teori dan Aplikasi Fisika, 2024)
The use of high-intensity non-automatic weighing instruments can cause users to overlook the load's location during weighing. However, electronic non-automatic weighing instruments maintain measurement accuracy regardless of the load's position. This study aims to analyze the effect of load receptor size on error values when testing non-automatic weighing instruments eccentricity using the OIML R-76 recommended method. Testing the eccentricity of electronic non-automatic weighing instruments with the same construction model, load cell, and indicator but different load receptor sizes can affect the non-automatic weighing instruments' error values. The largest error value on Instrument A, with a load floor size of 40x30cm, is -0.025kg at test point 4. On Instrument A, the smallest error value at test points 1, 2, and 5 is -0.005kg. On Instrument B, with a load floor size of 60x50cm, the largest error value at test points 1 and 4 is -0.005kg, respectively. At test points 2-3-5, the smallest error value on Instrument B is 0kg. The average error on Instrument A is -0.01kg, while on Instrument B it is 0kg. The size of the load receptor affects the increase in the error value of a non-automatic weighing instrument, with larger load receptor resulting in greater error values, even if the construction design of the load receptor support is the same.